Reference pricing with endogenous generic entry - Brekke, Kurt R. (2015)
In this paper we study the effect of reference pricing on pharmaceutical prices and ex-penditures when generic entry is endogenously determined. We develop a Salop-type model where a brand-name producer competes with generic producers in terms of prices. In the market there are two types of consumers: (i) brand biased consumers who choose between brand-name and generic drugs, and (ii) brand neutral consumers who choose between the different generic drugs. We find that, for a given number of firms, reference pricing leads to lower prices of all products and higher brand-name market shares compared with a reimbursement scheme based on simple coinsurance. Thus, in a free entry equilibrium, the number of generics is lower under reference pricing than under coinsurance, implying that the net effects of reference pricing on prices and expenditures are ambiguous. Allowing for price cap regulation, we show that the negative effect on generic entry can be reversed, and that reference pricing is more likely to result in cost savings than under free pricing. Our results shed light on the mixed empirical evidence on the effects of reference pricing on generic entry.